(untitled) (KULT_online, 2021)
Connectedness: An Incomplete Encyclopedia of the Anthropocene, edited by Marianne Krogh, offers an engaging journey through the many facets of the concept of the Anthropocene by presenting an original selection of almost a hundred keywords regarding it. Through the voices of relevant contemporary personalities, including A-list scholars, artists and architects, this non-conventional encyclopedia pursues a pluralistic standpoint – both in its organization and its contents – which establishes it as a useful tool for navigating the complexities of current ecological crises.